2015
DOI: 10.1073/pnas.1508543112
|View full text |Cite
|
Sign up to set email alerts
|

Rad51 recombinase prevents Mre11 nuclease-dependent degradation and excessive PrimPol-mediated elongation of nascent DNA after UV irradiation

Abstract: After UV irradiation, DNA polymerases specialized in translesion DNA synthesis (TLS) aid DNA replication. However, it is unclear whether other mechanisms also facilitate the elongation of UVdamaged DNA. We wondered if Rad51 recombinase (Rad51), a factor that escorts replication forks, aids replication across UV lesions. We found that depletion of Rad51 impairs S-phase progression and increases cell death after UV irradiation. Interestingly, Rad51 and the TLS polymerase polη modulate the elongation of nascent D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
67
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 68 publications
9
67
3
Order By: Relevance
“…Primer sequences were as follows: USP1 (Forward): 5’- GGACGCGTTGCTTGGAATGT-3’ (Reverse) 5’-TGCCCATCTCAGGGTCTTCA-3’. GADPH: (Forward) 5’-AGCCTCCCGCTTCGCTCTCT-3’ (Reverse) 5’-GAGCGATGTGGCTCGGCTGG-3’ (Vallerga et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Primer sequences were as follows: USP1 (Forward): 5’- GGACGCGTTGCTTGGAATGT-3’ (Reverse) 5’-TGCCCATCTCAGGGTCTTCA-3’. GADPH: (Forward) 5’-AGCCTCCCGCTTCGCTCTCT-3’ (Reverse) 5’-GAGCGATGTGGCTCGGCTGG-3’ (Vallerga et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Although the MRN nuclease function can help resolve stalled RFs, unregulated resection can be catastrophic and lead to fork degradation through MRE11 exonuclease activity (145, 146). Thus, other proteins help regulate MRN-mediated nascent DNA degradation (147150).…”
Section: Mrn and Replication Fork Dynamicsmentioning
confidence: 99%
“…Although the mechanism of DNA damage induction may look similar to that for APH, HU induces a different spectrum of fragile sites, called early replicating fragile sites (ERFs) [233]. ERFs are also induced by c-Myc expression [11,12]. It was also reported that 10 μg/mL APH [234] (concentration that stalls the replication fork progression) leads to the generation of several kilobases long unwound DNA; however, HU treatment can generate only up to 100–200 nt long ssDNA [235].…”
Section: Compoundsmentioning
confidence: 99%
“…The most common extrinsic sources of RS are all wavelengths of ultraviolet radiation (UV) [11], ionising radiation (IR) [12] and special genotoxic chemical compounds [13] which are the main focus of this review. RS-inducing chemicals can cause a broad spectrum of DNA lesions.…”
Section: Introductionmentioning
confidence: 99%